Charakterystyka wybranych metod pomiaru efektywności bazujących na krzywych efektywności - Kisielewska, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This paper introduces basics of frontier analysis methods that generally are ways to benchmark the relative performance of production units (commercial firms as well as non-profit institutions). The lack of agreement among researchers regarding a preferred frontier model at present boils down to a difference of opinion regarding the lesser of evils. Nevertheless, Berger and Humphrey reported roughly an equal split between applications of nonparametric techniques (69 applications) and parametric methods (60 applications) to financial institutions data. In Polish terms nonparametric approach is much more common so far (6 out of 8 studies under consideration). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 260-269